Impact of solid shrimp pond waste materials on mangrove growth and mortality: a case study from Pak Phanang, Thailand - Vaiphasa, C; de Boer, W. F; Skidmore, A. K; Panitchart, S; Vaiphasa, T; Bamrongrugsa, N; Santitamnont, P (Hydrobiologia, 2007)
One of the most serious threats to tropical mangrove ecosystems caused by shrimp farming activities is the poor management of pond waste materials. We hypothesise that mangroves can tolerate chemical residues discharged from shrimp farms and can be used as biofilters, but the capability of mangroves to cope with solid sediments dredged from shrimp ponds is limited. Our study in Pak Phanang, Thailand, confirmed that the excess sediments discharged from nearby shrimp ponds reduced mangrove growth rates and increased mortality rates. A series of transformed multi-temporal satellite images was used in combination with the field data to support this claim. In addition, a comparison between four dominant mangrove species revealed that Avicennia marina could tolerate sedimentation rates of >6 cm year-¹, while Bruguiera cylindrica tolerated sedimentation rates of 5 cm year-¹ (total sediment depth = 25 cm) before dying, while Excoecaria agallocha and Lumnitzera racemosa performed intermediate. This outcome implied that in our situation A. marina and to lesser extent E. agallocha and L. racemosa could be more effective as biofilters than B. cylindrica, as they may survive the sedimentation longer in the disposal areas. Further studies on the impact of sedimentation and chemical pollution of shrimp farm wastes on mangrove mortality and growth are required.